On iterated generating functions: A class of impossible sequences - Clapperton, James A.; Larcombe, Peter J.; Fennessey, Eric J. (Utilitas Mathematica, 2011)
We identify a class of sequences which are not achievable through the mechanism of iterated generating functions, aspects of which have been discussed in previous work by the authors.